The complexity of mating decisions in stalk‐eyed flies. Issue 17 (18th July 2017) - Chapman, Nadine C.; Siriwat, Penthai; Howie, James; Towlson, Aaron; Bellamy, Lawrence; Fowler, Kevin; Pomiankowski, Andrew
Abstract: All too often, studies of sexual selection focus exclusively on the responses in one sex, on single traits, typically those that are exaggerated and strongly sexually dimorphic. They ignore a range of less obvious traits and behavior, in both sexes, involved in the interactions leading to mate choice. To remedy this imbalance, we analyze a textbook example of sexual selection in the stalk‐eyed fly ( Diasemopsis meigenii ). We studied several traits in a novel, insightful, and efficient experimental design, examining 2, 400 male–female pairs in a "round‐robin" array, where each female was tested against multiple males and vice versa. In D. meigenii, females exhibit strong mate preference for males with highly exaggerated eyespan, and so we deliberately constrained variation in male eyespan to reveal the importance of other traits. Males performing more precopulatory behavior were more likely to attempt to mate with females and be accepted by them. However, behavior was not a necessary part of courtship, as it was absent from over almost half the interactions. Males with larger reproductive organs (testes and accessory glands) did not make more mating attempts, but there was a strong tendency for females to accept mating attempts from such males. How females detect differences in male reproductive organ size remains unclear. In addition, females with larger eyespan, an indicator of size and fecundity, attracted more mating attempts from males, but this trait did not alter female acceptance. Genetic variation among males had a strong influence on male mating attempts and female acceptance, both via the traits we studied and other unmeasured attributes. These findings demonstrate the importance of assaying multiple traits in males and females, rather than focusing solely on prominent and exaggerated sexually dimorphic traits. The approach allows a more complete understanding of the complex mating decisions made by both males and females. Abstract : All too often, studies of mating decisions focus on responses to single, exaggerated traits, typically in one sex only. They ignore a range of less obvious traits and behavior, both of males and of females, involved in the interactions leading to mate choice. To remedy this imbalance in the literature, we use a novel round‐robin array of 2, 400 male–female pairs to assay multiple traits including precopulatory behavior, reproductive organ size, and genetic variation, in relation to male mating attempts and female acceptance/rejection behavior, so as to understand the complex processes that lead to mating.